2014
DOI: 10.1016/j.clae.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Corneal cross-linking for Acanthamoeba keratitis in an orthokeratology patient after swimming in contaminated water

Abstract: Swimming in contaminated water might represent a risk for orthokeratology patients. CXL was effective for treating Acanthamoeba keratitis in an orthokeratology patient to eliminate active and cystic forms of the microorganism. Confocal microscopy was useful to confirm the diagnosis in the presence of confounding clinical signs observed during a conventional slit-lamp examination. Both CXL and confocal microscopy are essential to the outcome of PK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 32 publications
0
23
0
1
Order By: Relevance
“…It has been shown that swimming with lenses can increase the bacterial bioburden on lenses 22 and can expose the ocular surface to Acanthamoeba . Swimming has been identified as a likely factor for AK in GP wearers 23 , orthokeratology wearers 24 , frequent replacement SCL wearers 23 and daily disposable lens wearers. 25 Avoiding contact lens wear while swimming is the safest practice; however, if one chooses to swim while wearing reusable contact lenses, a pair of tight fitting goggles should be worn, thorough disinfection should occur in the evening 22 , and patients should be educated to be alert for signs and symptoms of infection after swimming.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that swimming with lenses can increase the bacterial bioburden on lenses 22 and can expose the ocular surface to Acanthamoeba . Swimming has been identified as a likely factor for AK in GP wearers 23 , orthokeratology wearers 24 , frequent replacement SCL wearers 23 and daily disposable lens wearers. 25 Avoiding contact lens wear while swimming is the safest practice; however, if one chooses to swim while wearing reusable contact lenses, a pair of tight fitting goggles should be worn, thorough disinfection should occur in the evening 22 , and patients should be educated to be alert for signs and symptoms of infection after swimming.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, the American Academy of Ophthalmology issued an official statement on the safety of orthokeratology, recommending a wide margin of safety for patients undergoing this therapy due to case reports of vision-threatening complications, such as infectious keratitis and milder complications of corneal erosions and iritis. 29 Since then, case reports and series have been published that noted a high incidence of Pseudomonas and Acanthamoeba species [30][31][32][33][34][35][36][37][38] and other gram-negative organisms including Serratia 39 from corneal isolates of infectious keratitis cases associated with orthokeratology use.…”
Section: Safety Concernsmentioning
confidence: 99%
“…Contact lens use in these environments has been acknowledged as a potential risk factor for developing ocular infection (Radford et al 2002;Choo et al 2005;Arance-Gil et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Negative bacterial and fungal cultures that do not improve with medical treatment should be further and immediately investigated. Confocal microscopy is useful to confirm the diagnosis of AK, considering that Acanthamoeba cultures usually show negative results (Choo et al 2005;Vaddavalli et al 2011;Arance-Gil et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation